2024
DOI: 10.1111/jav.03129
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐pair paternity enhances the reproductive fitness of urban Chinese blackbird

Xueli Zhang,
Zhen Zhang,
Wenjing Lu
et al.

Abstract: Urbanization is a human‐induced process of rapid habitat change that can affect the reproductive success of animals. The occurrence of extra‐pair paternity (EPP) may be sensitive to changes in urban ecological conditions. In this study, the Chinese blackbird Turdus mandarinus, a common breeding bird in southern Chinese cities, was selected as the focus species to explore the EPP patterns of monogamous birds in developing cities and the relationship between pairs. Over four breeding seasons, 316 Chinese blackbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
0
1
Order By: Relevance
“…Predation is a common cause of nest failure in birds, and other reasons for the failure include nest ectoparasites, bad weather, and human interference (Donahue et al., 2018 ). Although our study found a significant number of predation threats from aerial predators in urban habitats, the risk of urban predation was relatively low compared to rural or natural habitats (our findings in other comparative study of urban and rural Chinese blackbird, Zhang et al., 2024 ). Moreover, excellent permeability and ventilation ensure that breeding spotted dove reused nest in urban habitats are not at risk of large‐scale parasitic infections, which is supported by the fact that no breeding birds were detected to be parasitized during our investigation.…”
Section: Discussioncontrasting
confidence: 46%
“…Predation is a common cause of nest failure in birds, and other reasons for the failure include nest ectoparasites, bad weather, and human interference (Donahue et al., 2018 ). Although our study found a significant number of predation threats from aerial predators in urban habitats, the risk of urban predation was relatively low compared to rural or natural habitats (our findings in other comparative study of urban and rural Chinese blackbird, Zhang et al., 2024 ). Moreover, excellent permeability and ventilation ensure that breeding spotted dove reused nest in urban habitats are not at risk of large‐scale parasitic infections, which is supported by the fact that no breeding birds were detected to be parasitized during our investigation.…”
Section: Discussioncontrasting
confidence: 46%